A new species of the subgenus Tachycines (Gymnaeta) (Orthoptera: Rhaphidophoridae) from karst caves of southern Guizhou, China - Feng, Xueli; Huang, Shihui; Luo, Changqing (Zootaxa, 2019)
Some species of the subgenus Tachycines (Gymnaeta) inhabit caves. In this study, a new species of, Gymnaeta namely Tachycines (Gymnaeta) lalinus sp. nov., from two karst caves in Guizhou Province, China is described. This new species resembles the cave species Tachycines (Gymnaeta) zorzini from Guizhou Province, but can be separated from the latter by morphological characters of the male genitalia, the number of spines on hind tibiae, and coloration.